Dug Well Water Quality to Reduce Pollution Parameters Kapasa Village, Biringkanaya District, South Sulawesi - Idris, Idris; Lahming, Lahming; Muslimin, Muslimin; Yermi, Yermi; Marpaung, Mauritz Pandapotan; Adiaksa, Baso Witman (International Journal of Health Sciences, 2024)
The quality of dug well water should comply with established regulations. The pollution caused by bacteria to water in the ground widens to ± 2 meters at a distance of 5 meters from the source of pollution 3 and narrows to a distance of 11 meters in the direction of the ground flow. This type of research is descriptive research, namely to determine the use of silica sand filter media, activated carbon in filter reactors on reducing TDS, Nitrite (NO2), Dissolved Manganese and MPN Coliform by comparing the composition of the filter media with reference to clean water quality standards Permenkes No. 2 In 2023, the samples in this research were dug wells located in Kapasa Village, Biringkanaya District, Makaasar City. The results of this research after the filtration intervention of manganese media, activated charcoal and silica sand, found that TDS, color, Manganese Nitrite (NO3) had decreased levels of environmental pollution, this is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. Conclusions from the results research shows that silica sand, manganese and activated charcoal filtration media, TDS, manganese nitrate (NO2) and MPN Coliform can effectively reduce water pollution levels in dug wells in accordance with the Minister of Health Regulation. So the risk of infectious and non-communicable diseases can be overcome with the intervention of silica sand, manganese and activated charcoal filtration media.